Acute Massive Lower Gastrointestinal Bleeding Secondary to Obstructive Colitis Proximal to Obstructing Cancer of the Sigmoid Colon - Siow, Sze Li; Nyunt, Myo; Mahendran, Hans Alexander (Asian Journal of Case Reports in Surgery, 2021)
Introduction: Acute massive lower gastrointestinal bleeding (LGIB) is a rare and serious manifestation of obstructive colitis that requires urgent therapeutic intervention. Here, we report a case of LGIB due to obstructive colitis in an adult patient.